Horn clause techniques in rehabilitation clinic for return to work - Amr R.M.-N.A.; Zakaria L.Q.; Ismail R.; Bahari M.; Yusof M.M.; Waidah Ismail; Nurzi Juana Mohd Zaizi (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by SCOPUS